Chaos Based Joint Compression and Encryption Framework for End-to-End Communication Systems - Nidhi Goel; Balasubramanian Raman; Indra Gupta (Advances in Multimedia)
Augmentation in communication and coding technology has made encryption an integral part of secure multimedia communication systems. Security solution for end-to-end image transmission requires content adaptation at intermediate nodes, which consumes significant resources to decrypt, process, and reencrypt the secured data. To save the computational resources, this paper proposes a network-friendly encryption technique, which can be implemented in transparency to content adaptation techniques. The proposed encryption technique maintains the compression efficiency of underlying entropy coder, and enables the processing of encrypted data. Thorough analysis of the technique, as regards various standard evaluation parameters and attack scenarios, demonstrates its ability to withstand known-plaintext, ciphertext-only, and approximation attacks. This justifies its implementation for secure image transmission for end-to-end communication systems.